Upaya Peningkatan Pemasaran Produk Bank Sampah Melalui Pelatihan Digital Marketing - Afni Ma'rufah; Ema Zulfa Nihayati; Melina Rahayu Awalliya (Abdimas Indonesian Journal, 2022)
This article aims to find out the right marketing strategy for the Waste Bank. The Indah Pemadani waste bank is located in Nambak Village, Bungkal District, Ponorogo Regency which was established in early 2020. The establishment of this Waste Bank was motivated by the large amount of waste that had piled up in Nambak Village. With the Indah Permadani Waste Bank, waste is managed into various products including tissue containers and bags made from aqua bottle waste. However, in the management of the Indah Permadani Waste Bank, there are obstacles in the field of product marketing. Where the products produced are only sold at bazaars and certain events such as “the Krempyeng market”. This article uses an Asset Based Community Development (ABCD) approach that prioritizes the utilization of assets and potentials that are around and owned by the community. One of the results of this article is an increase in the marketing of waste bank products through digital marketing which is useful and of course able to develop community skills in product management.